2016
DOI: 10.1093/europace/euw192
|View full text |Cite
|
Sign up to set email alerts
|

The slope of the initial temperature drop predicts acute pulmonary vein isolation using the second-generation cryoballoon

Abstract: About 25 s after freeze initiation, the temperature-time slope predicts important key characteristics of a cryoablation, such as nadir temperature. The slope is the only reported predictor to actually precede acute isolation and thus to support decisions about pull-down manoeuvres or aborting a cryoablation early on. It is also predictive of very low nadir temperatures and phrenic nerve palsy and thus may add to patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Many previous reports have stated that it is difficult to obtain a complete occlusion of the RIPV [2,6,12,13] . In a PVI based on the CB, we usually position the CB so that the CB can evenly adhere to the PV orifice.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous reports have stated that it is difficult to obtain a complete occlusion of the RIPV [2,6,12,13] . In a PVI based on the CB, we usually position the CB so that the CB can evenly adhere to the PV orifice.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that thawing rate was a novel predictor of acute PVI, which could provide a certain reference value when factors such as cryoablation temperature and time cannot effectively predict PVI. Deubner et al found that a 20-second time frame with a freezing rate of <17°C could best predict PVI ( 21 ). Meanwhile, our study showed that the ITR15 was the most valuable predictor of acute PVI.…”
Section: Discussionmentioning
confidence: 99%
“…Cryoablation curves from 592 cryoablations were reconstructed using these data ( Figure 1A ). Our aim was to quantify the thawing rate by fitting a regression line to a specific portion of the cryoablation curve ( 21 ). The slope of the regression line ( Figure 1B ) provided an immediate measure of the rapidity of the temperature rise.…”
Section: Methodsmentioning
confidence: 99%
“…Recent articles have highlighted the importance of temperature attainment as a predictor of successful PV isolation. Deubner et al [13] interestingly demonstrated that a steeper temperature slope descent in the first instances of the freeze proved to reliably predict acute PV isolation. In addition, Iacopino et al [11] showed comparable clinical outcomes between a traditional approach with an ILMC and an ablation strategy solely guided by temperature in the setting of second generation CB ablation.…”
Section: Discussionmentioning
confidence: 99%